Bargaining power and outside options in the interbank lending market - Puriya Abbassi; Falk Bräuning; Niels Schulze (Deutsche Bundesbank, 2017)
We study the role of bargaining power and outside options for the pricing of over-the-counter interbank loans using a bilateral Nash bargaining model and test the model predictions with detailed transaction-level data from the euro-area interbank market. We find that lender banks with greater bargaining power over their borrowers charge higher interest rates, while the lack of alternative investment opportunities for lenders reduces bilateral interest rates. Moreover, we find that lenders that are not eligible to earn interest on excess reserves (IOER) lend funds below the IOER rate to borrowers with access to the IOER facility, which in turn put these funds in their reserve accounts to earn the spread. Our findings highlight that this persistent arbitrage opportunity is not a result of the mere lack of alternative outside options of some lenders, but it crucially depends on their limited bilateral bargaining power, leading to a persistent segmentation of prices in the euro interbank market. We examine the implications of these findings for the transmission of euro-area monetary policy.
Keywords: E4; E58; G21; 330; bargaining power; over-the-counter market; monetary policy; money market segmentation